The Role of Fintech Encourages the Export of Small Medium Enterprises in Indonesia - Ragimun -; Sri Yanthy Yosepha (Journal of Social and Development Sciences, 2018)
At present the development of financial technology (fintech) in Indonesia is very fast, many nonbank companies practice as fintech executors who channel loans to the public or Small Medium Enterprise (SMEs), this has the potential to lead to illegal banking practices (shadow banking). The next problem is how the government makes rules that can synergize fintech with the business world, banking, SMEs and others. In the future, it is expected that Fintech will play an active role in encouraging the export of the SME sector which is Indonesia's flagship sector. In this study a qualitative descriptive approach was used, which emphasized the discussion by examining the role of fintech to encourage the export of small and medium industries in Indonesia. Data sources that can be used are data from the Central Statistics Agency (BPS), the Financial Services Authority (OJK), Bank Indonesia and various relevant data sources. Fintech is currently very helpful in helping the financial literacy of the Indonesian people including SMEs as a mainstay of increasing exports in Indonesia. Several obstacles to the spread of the role of fintech continue to be overcome through various means including infrastructure improvements, socialization and financial literacy to the public and SMEs and fintech regulatory policies. The government needs to make harmonious rules to grow and to avoid risks in the financial services industry. This is crucial because the development of fintech in Indonesia is very fast. Licensing for the establishment of fintech companies from other countries must be monitored.